MOTIVASI PENONTON VICE INDONESIA DENGAN KETERIKATAN MENONTON - Mahardika, Bernardus Aji; Safira, Mazaya Rizy (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
YouTube is a social media platform that offers a wide variety of video content, providing entertainment and information to its users. One of the media channels on YouTube is Vice Indonesia, which observes the evolution of mass media from traditional to digital platforms. This study aims to investigate the correlation between viewing motivation and watching attachment among viewers of Vice Indonesia content. A quantitative approach is utilized, and data is collected through an online survey. The research sample consists of 100 respondents who are viewers of Video Vice Indonesia content. Statistical Analysis Techniques, using the Statistical Standard Solution Program (SPSS), are employed for data analysis. The research findings and hypothesis testing reveal that the calculated r value for the relationship between motivation (X) and attachment (Y) is 0.510, which is greater than the critical r-table value of 0.195. Therefore, it can be concluded that there is a significant correlation between the motivation variable and the attachment variable. This result indicates a promising avenue for further research to explore the impact of viewing motivation on viewing engagement, particularly in documentary content.